Lives unremembered : the Holocaust and strategies of its representation : an exegesis presented in partial fulfillment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Rajala, Tero Markus (Massey University, 2008)
The Holocaust is a subject that seems to defy artistic representation by way of its sheer scale of tragedy and subsequent trauma. As I will demonstrate in this paper, it is hard to restore visibility – pictorial links between past and present realities – to crimes that have been deliberately submerged by its perpetrators. I will examine some of the common strategies used in representation of the victims of the Holocaust since the end of the Second World War, in the mediums of film and photography. As my main method of enquiry, I will examine three films from different eras, and of very different approaches in terms of their processing of the proposed original evidence, as examples to illustrate my arguments. In the second chapter Alain Resnais's documentary film Nuit et Brouillard (Night and Fog) is analyzed as a birthplace of the so-called iconography of the Holocaust. Chapter three examines workings of memory through the aesthetic form that was soon to follow; the role and testimony of the survivors is considered through Claude Lanzmann's Shoah. In the fourth chapter a new player is introduced: the second generation witness of postmemory, works of transmitted but unexperienced realities. In this chapter I will closer examine the workings of art in the game of reprocessing the evidence of the Holocaust, and through Dariusz Jablonski's film Fotoamator I aim to critique how the previously discussed approaches serve to further lock the Holocaust in an inaccessible canon. Moreover, the generalization implied – a drive toward universalization of the Holocaust as an idiom or even a metaphor for the dark sides of human history/character – derives from problems of representation; mainly that of anonymity in face of the proposed beauty of the spectacle, of tragedy and suffering in mass-media. A key problem is that any historical document, however we define one, is considered transparent and unmediated, whereas art is clearly something where a degree of mediation is necessarily recognized. In the face of this dichotomy it seems that all the collected "proof" of the Holocaust – witness accounts" photographs" films" material remains – achieves, is to stregthen the prevailing version of history.
Keywords: Holocaust; Film; Nuit et Brouillard; Night and Fog; Shoah (movie); Fotoamator; Fields of Research::410000 The Arts::410300 Cinema, Electronic Arts and Media Studies::410301 Film and video studies